Challenges to Implementing the New Homelessness Prevention Agenda in Wales. Issue 1 (January 2020) - Ahmed, Anya; Madoc-Jones, Iolo; Gibbons, Andrea; Jones, Katy; Rogers, Michaela; Wilding, Mark
Abstract : Devolution presented an opportunity for the Welsh Government to introduce changes to housing and homelessness policy, and the subsequent homelessness reforms are seen as one of the best examples to date of the Welsh Government using its powers. However, devolved governments in small countries face a number of challenges in terms of realising their housing policy ambitions. In this article we argue that there is inevitable dissonance between the policy behind the Welsh Government legislation (prevention) and practice (implementation) associated with structural challenges (for example, austerity and budget restrictions, Welfare Reform and the availability of affordable accommodation). In response we propose a number of actions the Welsh Government might undertake to attempt to mitigate such structural challenges which also resonate in the English context where welfare retrenchment and homelessness prevention policies operate simultaneously.